2015
DOI: 10.1007/s12072-015-9675-4
|View full text |Cite
|
Sign up to set email alerts
|

Asian-Pacific clinical practice guidelines on the management of hepatitis B: a 2015 update

Abstract: Worldwide, some 240 million people have chronic hepatitis B virus (HBV), with the highest rates of infection in Africa and Asia. Our understanding of the natural history of HBV infection and the potential for therapy of the resultant disease is continuously improving. New data have become available since the previous APASL guidelines for management of HBV infection were published in 2012. The objective of this manuscript is to update the recommendations for the optimal management of chronic HBV infection. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
2,812
3
35

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,147 publications
(3,023 citation statements)
references
References 652 publications
(730 reference statements)
26
2,812
3
35
Order By: Relevance
“…Another study conducted on a Chinese population, the IL-18 -137 SNP with C allele was shown to be associated with protection against HBV infection [20]. The IL-18-137G/C polymorphism, but not the -607A/C polymorphism, showed a significant association with the risk of hepatocellular carcinoma [21]. Moreover, the IL-18-607 SNP with AA genotype was accompanied by inhibition of HBV DNA replication [20].…”
Section: Discussionmentioning
confidence: 97%
“…Another study conducted on a Chinese population, the IL-18 -137 SNP with C allele was shown to be associated with protection against HBV infection [20]. The IL-18-137G/C polymorphism, but not the -607A/C polymorphism, showed a significant association with the risk of hepatocellular carcinoma [21]. Moreover, the IL-18-607 SNP with AA genotype was accompanied by inhibition of HBV DNA replication [20].…”
Section: Discussionmentioning
confidence: 97%
“…1 Hepatocellular carcinoma (HCC) accounts for more than 80% of PLC, and more than half of HCC cases in China are caused by hepatitis B virus (HBV). 2,3 Although HBV is the most prominent etiology associated with HCC development, it is not directly involved in hepatocarcinogenesis. The pathogenesis of HBV-associated HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This is accompanied by a significant decrease in the incidence of infant fulminant hepatitis associated with chronic liver disease, mortality, and HCC [14,15].…”
Section: Epidemiologymentioning
confidence: 99%
“…Antiviral therapies including lamivudine, adefovir dipivoxil, entecavir, telbivudine, tenofovir, and Peg-interferon have been widely prescribed for the treatment of HBV-related liver diseases worldwide [14,31,32]. Several large population-based and international studies have reveal that antiviral therapy could reduce the incidence of hepatic failure, cirrhosis, HCC, and mortality in CHB patients without alcoholism [33][34][35][36][37][38][39][40].…”
Section: Treatment In Patients With Concomitant Hbv Infection and Alcmentioning
confidence: 99%